Randomized controlled trial of Phyllanthus niruri Linn extract - Patria Vittarina Sarisetyaningtyas; Sri Rezeki Hadinegoro; Zakiudin Munasir (Indonesian Pediatric Society Publishing House, 2016)
Background Clinical benefits of antiviral treatment in children experience varicella without complications, remains controversial. Phyllanthus niruri Linn extract as a natural medicine is used to increase cellular and humoral immunity. Objective To determine the efficacy and safety of Phyllanthus niruri Linn extract in the treatment of varicella in children compared to placebo. Methods This was a double-blind randomized controlled trial on children ages 2-14 years who experienced varicella without com- plications. Subjects were randomly assigned to receive either Phyllanthus niruri Linn extract syrup (5 mg/5ml, 3 times daily) or placebo. Efficacy was measured by calculating the number of pap- ules and crusts after taking the extract for 4 days of administration. A five-day monitoring sheet to record daily follow up and adverse effects of the subjects were given to their parents. Results Efficacy of Phyllanthus niruri Linn measurement based on no more new papules occurred at the five-day monitor was de- tected in 46 subject (51.1%) of the Phyllantus niruri Linn group compared to the placebo group (P=0.723). Meanwhile, the differ- ence of efficacy based on time of crusts disappear in Phyllanthus niruri Linn and placebo group were 22 subjects (43.1%) and 15 subject (30.0%), respectively (P=0.053). This finding proved have clinical benefit (NNT=7.6). Conclusion There was no significant difference between the ef- ficacy of Phyllanthus niruri Linn and placebo in terms of the pre- vention appearing new papules and crusts. However, clinically Phyllanthus niruri Linn accelerates appearing and aborting crust compared to placebo